Turf Toe Injury: A Pictorial Review and a Didactic Case Report - Claikens, Tom; Rezaie, Wahid; Simons, Philip (Seminars in Musculoskeletal Radiology, 2024)
Hyperextension of the first metatarsophalangeal joint can lead to a turf toe injury of the plantar plate complex, resulting in significant morbidity for athletes. This article reviews the anatomy, pathophysiology, classification, and imaging findings of turf toe injuries. In turf toe trauma, many different structures can be injured, with the sesamoid-phalangeal ligaments the most common. Diagnosis, classification, and treatment options rely on clinical evaluation and specific magnetic resonance imaging findings. It is vital for radiologists to understand the anatomy, pathophysiology, and imaging findings of turf toe injuries to ensure an accurate diagnosis and appropriate management.
Keywords: turf toe; first metatarsophalangeal joint; plantar plate complex; sesamoids